Scheduled Commercial Banks (SCBs) of India: A Study on Key Performance Indicators (KPIs) - Afreen Begum; Mohd. Razaullah Khan (PT Keberlanjutan Strategis Indonesia, 2026)
The authors of this paper establish metrics for assessing a few chosen financial KPIs of Indian commercial banks. The study analyzed data from commercial banks for the years 2019–20 to 2022–2023 using Key Performance Indicators. Financial performance was measured using six indicators: financial performance, operational efficiency and cost management, asset quality and credit risk, liquidity and funding, regulatory compliance, diversification, and income mix KPIs. Payment Banks and Public Sector Banks are required to manage core operations to increase profitability efficiently. Inefficient investment portfolios, high employee costs, and reliance on costlier deposits are issues for Payment Banks. Small Finance Banks have the highest COD, and potentially lower net interest margin, while Payment Banks have higher cost control. Foreign Banks and Payment Banks have excessive liquidity and possible underutilization of funds. PvSBs, Foreign Banks, and All Schedule Commercial Banks are not meeting regulatory targets for lending to the priority sector. The efficient performance of banks is the essence of the robust financial and economic system of the country. Effective implementation of financial policies ensures better control and better performance of banks by KPIs and maintains the highest level of financial stability, which would improve the further expansion of the financial performance of the banks. The authors offer a KPI-based measure of financial performance that incorporates sub-indicators from the Broad Six KPIs.